Copper-Catalyzed Ring Opening of Furans as a Concise Route to Polysubstituted Furans under Mild Conditions - Yin, Biaolin; Yu, Huiyue; Li, Zhengrong; Zhong, Weiqiang; Gu, Wenxiang (Synthesis, 2012)
A range of polysubstituted furans were synthesized from furan derivatives involving copper-catalyzed ring opening of the furan ring. This synthetic method possesses the advantages of readily available starting materials, mild reaction conditions, and short steps.
Keywords: polysubstituted furan; ring-opening of furan; ring-opening/rearomatization; copper-catalyzed